Viscometric behavior of banana (Musa acuminata var. cavendishii) puree - Sonido, Divina G.
The study aimed to determine the effecs of ripeness level. concentration of solids and temperature on the viscometric behavior of banana puree. Viscometric measurements were made with a Brookfield synchroelectric viscometer model LVT. The viscometric constants namely, yield stress (C), fluid behavior index (s) and fluid consistency coefficient (b) were computed using a power law model. The values obtained showed that banana puree was pseudoplastic with non-zero yield stress. The values of the constants were statistically analyzed for significant differences, using analysis of variance and Duncan's Multiple Range tests. The results indicated that yield stress values were significantly affected by solids concentration, ripeness level and temperature. Yield stress values increased with increases in solids content and decreased with ripeness level. At higher temperatures, a decrease in yield stress value was observed. Statistical analysis, however showed that differences in yield stress at 140°F and 160°F were not significant. Fluid behavior indices were all less than unity. The magnitude of fluid behavior indices decreased with increasing solids content and increased with elevation in temperature and with ripening. Statistical analysis indicated relative to ripeness level, differences in fluid behavior indices between table ripe and over ripe sample were not significant. With regards to temperature and solids content, the fluid behavior indices of all samples were significantly different from each other. Fluid consistency coefficients increased with increasing solids content and decreased with elevation in temperature and with ripening. Results of the statistical analysis indicated that fluid consistency coefficients of the table ripe and over ripe samples were not significant. Fluid consistency of coefficients of the samples with 16% solids was also not significantly different from fluid consistency coefficients of samples with 18% solids. The fluid consistency coefficient of the samples at 160°F was not significantly different from that at 140°F and that at 140°F was also significantly different from 180°F. The apparent viscosity at shear rates of 10 - 1000/sec. were computed using the power law equation. Line graphs were made to illustrate the effects of temperature and shear rate on apparent viscosity. The apparent viscosity was shown to decrease with increasing shear rates. Effect of temperature was largely attributed to two factors namely, gelatinization of starch and greater movement of molecules due to application of heat. The relationship between apparent viscosity (y) and % starch (x) were computed using the power law equation: y = ax^b. Variation of apparent viscosity with starch content had significant correlation at 180°F in all ripeness levels and the over ripe stage in all temperatures.